2023
DOI: 10.1101/2023.07.18.549179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning generalizable visuomotor mappings for de novoskills

Carlos A. Velázquez-Vargas,
Nathaniel D. Daw,
Jordan A. Taylor

Abstract: A fundamental feature of the human brain is its capacity to learn novel motor skills. This capacity requires the formation of vastly different visuomotor mappings. In this work, we ask how these associations are formed de novo, hypothesizing that under specific training regimes generalizable mappings are more readily formed, while in others, local state-actions associations are favored. To test this, we studied learning in a simple navigation task where participants attempted to move a cursor between various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Studies across various learning tasks suggest that greater variability produces worse performance during training but better memories/generalization (Raviv et al, 2022). A recent study in a grid-sailing, key press task suggested that more variable training leads to better knowledge of novel action outcome pair mappings (Velázquez-Vargas et al, 2023). Therefore, it is possible that by exploring the space, individuals in the RPE group developed better knowledge of the action outcome pair.…”
Section: Discussionmentioning
confidence: 99%
“…Studies across various learning tasks suggest that greater variability produces worse performance during training but better memories/generalization (Raviv et al, 2022). A recent study in a grid-sailing, key press task suggested that more variable training leads to better knowledge of novel action outcome pair mappings (Velázquez-Vargas et al, 2023). Therefore, it is possible that by exploring the space, individuals in the RPE group developed better knowledge of the action outcome pair.…”
Section: Discussionmentioning
confidence: 99%